ANALISIS STRATEGI PEMASARAN MELALUI PENINGKATAN KUALITAS PELAYANAN DAN IMPLIKASINYA TERHADAP KEPUTUSAN PEMBELIAN PADA HOTEL SANTIKA BANGKA - Paramika, Sia; Zamhari; Ruben Manullang, Rizal (Jurnal Progresif Manajemen Bisnis, 2019)
The purpose of this research is to know the influence of Reliability, Responsibility, Competence, Access, Courtesy, Communication, Credibility, Security, Understanding, and Tangibles on buying decision either partially or simultaneously at Hotel Santika Bangka. This study uses quantitative data analysis, and multiple linear regression. As a tool in the processing of statistical data used JASP versi 0.9.2.0 Universiteit-van-amsterdam program. On the partial result using t test, Reliability positively influences on buying decision, Responsibility not positively influences on buying decision, Competence positively influences on buying decision, Access positively influences on buying decision, Courtesy positively influences on buying decision, Communication positively influences on buying decision, Credibility positively influences on buying decision, Security positively influences on buying decision, Understanding not positively influences on buying decision and Tangibles positively influences on buying decision. The results of this research using F-test of ten dimensions of increase service quality also positively affect together to buying decision. Based on result of this research, coefficient of determination (adjusted r-square) is 0,721. This value can be defined that 72,1% buying decision variabel can be explained by dimension of service quality like Reliability, Responsibility, Competence, Access, Courtesy, Communication, Credibility, Security, Understanding, and Tangibles, and the remaining 27,9% influenced by other variables npt included in this research.